Ethical context of legally regulated surrogate and genetic motherhood in Russia - I. V. Siluyanova (Акушерство, гинекология и репродукция, 2021)
Aim: to assess the compliance of legal norms regulating surrogate motherhood and moral concepts about motherhood and childhood in society.Materials and Methods. The Articles 55 (clause 9) of the Federal Law "On the Fundamentals of Health Protection of Citizens in the Russian Federation", the principles of the Constitution of the Russian Federation, and traditional moral concepts common in society of the Russian Federation underwent a comparative analysis.Results. Discrepancies between moral and legal norms were revealed in 3 issues. Issue 1 is related to the rights for surrogacy of unmarried persons and the rights of single citizens. In an ethical context, the statement of their rights does not correspond to the rights of children to a dignified upbringing in a family composed of a mother and father. Issue 2 refers to the ethical incorrectness of compensated surrogacy contracts. Commercial surrogacy cannot be separated from transformed forms of child trafficking. Issue 3 is related to the moral degradation of motherhood upon using technologies of surrogate and genetic motherhood.Conclusion. It is necessary to conduct additional studies on using surrogate motherhood in order to prevent abuse and violations upon its application in Russia as well as open up a public discussion on this matter.